Exposure to blue wavelength light modulates anterior cingulate cortex activation in response to 'uncertain' versus 'certain' anticipation of positive stimuli. (11th March 2016) - Alkozei, Anna; Smith, Ryan; Killgore, William D.S.
Highlights: We compared the effects of thirty minutes of blue versus amber light exposure. Participants completed an emotional anticipation task after the light exposure. 'Uncertain event' > 'certain reward' led to lower activation for blue vs. amber. Blue light may improve adaptive learning-related synaptic processing within the ACC. Abstract: Blue wavelength light has been used as an effective treatment for some types of mood disorders and circadian rhythm related sleep problems. We hypothesized that acute exposure to blue wavelength light would directly affect the functioning of neurocircuity implicated in emotion regulation (i.e., ventromedial prefrontal cortex, amygdala, insula, and anterior cingulate cortex [ACC]) during 'certain' and 'uncertain' anticipation of negative and positive stimuli. Thirty-five healthy adults were randomized to receive a thirty-minute exposure to either blue (active) or amber (placebo) light, immediately followed by an emotional anticipation task during functional magnetic resonance imaging (fMRI). In contrast to placebo, participants in the blue light group showed significantly reduced activation within the rostral ACC during 'uncertain' anticipation (i.e., uncertainty regarding whether a positive or negative stimulus would be shown) in comparison to 'certain' anticipation of a positive stimulus. These findings may be explicable in terms of interactions between blue light exposure and the influence of specific neuromodulators on ACC-mediated decision-making mechanisms.